Assessing hydrological alterations in a tropical basin using an adaptation of the ELOHA framework - THAMIRIS FONTOURA DE ARAUJO (2024)
A better understanding of the interplay between ecological responses, climate variability, and water resources management provides a robust resource for policymakers in refining environmental flow targets. However, studies encompassing streamflow alterations and their impacts on environmental flow targets are still scarce in many countries, especially under climate change scenarios. Here, the impacts of climate change on streamflow in a tropical watershed covering 362 km² in midwestern Brazil, which supplies water to nearly 34% of the approximately 900 thousand inhabitants, were investigated using an adapted version of the Ecological Limits of Hydrologic Alteration (ELOHA) framework. The hydrological physically based SWAT+ model was used and calibrated to simulate the watershed’s hydrological response to three climate change scenarios from the seven General Circulation/Earth System models (GCM/ESM) provided by the Coupled Model Intercomparison Project phase 6: SSP2-4.5 (moderate forcing), SSP3-7.0 (moderate to high forcing), and SSP5-8.5 (high forcing). The SSP2-4.5 and SSP3-7.0 exhibited the greatest hydrologic alterations in the median flows from 2015 to 2100, reaching a high alteration degree of 0.71 and 0.67, indicating higher frequency in high flow values; the SSP5-8.5 and baseline are mostly alike in terms of median flows despite the hydrologic alteration reaching a moderate alteration degree of -0.51. The findings show an increasing trend in median flow over the future period in the three scenarios due to an increase in the frequency of extreme flood events. The SSP5-85 exhibited the most vulnerability to an extreme low flow event. It was observed an average of 142 (SSP2-4.5), 150 (SSP3-7.0), and 136 days (SSP5-8.5) of low precipitation (< 1mm) to trigger periods of extreme low flow, which are streamflow values lower than 10% of daily flows for the period on the basin. According to the scenarios, shifts in hydrological frequencies showed a stronger correlation to precipitation patterns than to evapotranspiration. The hydrological shifts in the frequency of floods and droughts impacts on the life cycles of species, community diversity, and habitat conditions (including temperature, dissolved oxygen levels, and accessibility for aquatic and terrestrial species). Moreover, these changes have significant implications for water service management, requiring continuous revisions of water plans and regulations due to the variability in the streamflow and water quality. This study also highlights the challenges of fully implementing the framework in Brazil, as well as emphasized the importance and the need of similar research to enhance water resources management and decision making, mainly in the context of water insecurity. Keywords: Hydrological Changes; Water supply; Future Projections.